Understanding the 2015 marriage referendum in Ireland: context, campaign, and conservative Ireland. Issue 3 (3rd July 2017) - Elkink, Johan A.; Farrell, David M.; Reidy, Theresa; Suiter, Jane
ABSTRACT: On 22 May 2015 the marriage referendum proposal was passed by a large majority of Irish voters and the definition of marriage in the constitution was broadened to introduce marriage equality. This referendum is remarkable for a number of reasons: (1) it is uniquely based on an experiment in deliberative democracy; (2) the referendum campaign was unusually vigorous and active; and (3) the voting patterns at the referendum point to a significant value shift along the deep seated liberal conservative political cleavage of Irish politics. This article provides an overview of the background to the referendum initiative, the campaign prior to the referendum, and the key factors that drove voter turnout and preference. Based on a post-referendum survey, we find that while support for the government of the day, political knowledge, and social attitudes have the same effects as commonly found in other referendums, the variation among social classes was less prevalent than usual and door-to-door canvassing by the two sides of the campaign impacted through turnout rather than vote preference. The voting behaviour of the different age groups suggests strong generational effects.